MODERN REQUIREMENTS OF INTERNATIONAL AIRLINES TO AVIATION ENGINEERS - Mikheyeva, Tamara (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The article considers the forecasts of Boeing Corporation on the growth of demand for aviation specialties. A theoretical analysis of the requirements of international airlines to aviation engineers is carried out. In accordance with the modern requirements of the international labor market, the skills necessary for aviation engineers for successful and effective professional activity are highlighted.